Remember the Land - Eng, Brent (Religion and society, 2024)
In a provocative section entitled "A Reading of Origins: Myth, Truth, and Power" in Chapter 1 of Formations of the Secular, Talal Asad cites European Enlightenment attitudes toward mythology: But as Jean Starobinski reminds us, myth was more than a decorative language or a satirical one for taking a distance from the heroic as a social idea. In the great tragedies and operas of the seventeenth and eighteenth centuries, myths provided the material through which the psychology of the human passions could be explored. (2003: 29)